New Methods of Monitoring Glycemia - Helwick, Caroline (MD Conference Express, 2007)
Average blood glucose may accurately reflect a patient’s daily variations in blood glucose, and may be a number that is easier for patients to understand than HbA1C. These findings from an international study support the recent agreement among diabetes organizations worldwide to standardize how HbA1C test results are reported.